Formulated hydroxy fatty acids from fruit pomaces reduce apple scab development caused by Venturia inaequalis through a dual mode of action - Gaucher, Matthieu; Juillard, Anthony; Nguyen, Bao-Huynh; Viller, Noémie; Ernenwein, Cédric; Marion, Didier; Brisset, Marie-Noëlle; Bakan, Bénédicte (Frontiers in Plant Science, 2024)
The outermost hydrophobic layer of plants, i.e. the cuticle, is mainly composed of cutin, a polyester of hydroxy fatty acids with reported eliciting and/or antimicrobial activities for some of them. By-products of the fruit processing industry (fruit pomaces), often strongly enriched in cuticular material, are therefore a potential source of bioactive compounds for crop protection against pathogen attack. We investigated the utilization of tomato and apple pomaces in the development of a cutin-based biocontrol solution against apple scab, a major apple disease caused by Venturia inaequalis. Several cutin monomer extracts obtained through different strategies of depolymerization and purification were first compared for their ability to induce a targeted set of defense genes in apple seedlings after foliar application. After a step of formulation, some extracts were chosen for further investigation in planta and in vitro. Our results show that formulated cutin monomers could trigger a significant transcriptome reprogramming in apple plants and exhibit an antifungal effect on V. inaequalis. Cutin monomers-treated apple seedlings were significantly protected against infection by the apple scab agent. Altogether, our findings suggest that water-dispersed cutin monomers extracted from pomaces are potential new bio-based solutions for the control of apple scab.